ОИЛАДА БОЛАЛАРДА ГЎЗАЛЛИК ФАЗИЛАТЛАРИНИ РИВОЖЛАНТИРИШ - Абдимуратов, Ж.П. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of development in the family children’s ability to value beauty, spiritual environment, study of a person as a social value and ways of enrichment and development of the ancestors’ heritage